THE ROLE OF THE DISTRICT GOVERNMENT INTEGRATED TEAM IN RESOLVING LAND CONFLICTS BETWEEN CORPORATIONS VS SUKU ANAK DALAM - Hijriah, Nurul Khoirotul (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
This study aimed to determine the role and mechanism of the integrated Team in Batang Hari Regency in resolving land conflicts between PT.Berkat Sawit UtamaÂ with the 113 Anak Dalam Tribe in Bungku Village, Batang Hari Regency. The role of the Batang Hari Regency Integrated Team is regulated in the Batang Hari Regency Regional Regulation Number 72 of 2022 concerning the establishment of an Integrated Team for Social Conflict Resolution at the Batang Hari Regency Level in 2022, which is regulated in Permendagri No. 42 of 2015 concerning Implementation of Coordination of Handling Social Conflicts. This research method is empirical juridical because it uses secondary data as supporting data and primary data collected through literature and field research. Based on the results of the study, it can be concluded that the Batang Hari District Integrated Team in resolving land conflicts between PT.Berkat Sawit Utama with the SAD 113 group, namely by facilitating, mediating, and maximizing the dispute resolution process through the establishment of the Batang Hari Regent's Decree Number 72 of 2022 concerning the establishment of an Integrated Team for handling social conflict at the Batang Hari Regency level in 2022. This integrated Team carried out the settlement, considered ineffective for both parties, where the conflict that should have been resolved became hampered and prevented both parties from obtaining legal certainty regarding this land dispute. Therefore, it is necessary for a party that has higher authority than the district government, which has limitations because of the regional autonomy system, to participate in settling land dispute cases